“At Last a Practical Man Got a Gun”: The Masculinity of Children’s Aid, 1893–1912 - Reid, Mike (Ontario History)

(untitled) (The Ontario Historical Society, 2011)
Throughout the nineteenth century, Ontario child saving had been largely a women’s domain. But Children’s Aid Societies (CASs), appearing in the 1890s, were consistently dominated by men. This article explores the gendered meaning that CAS work held for the people who performed it and the relationship between that meaning and the actual practice of the work. Research in the archives of three Ontario CASs — those of Ottawa, Brantford, and especially Belleville — indicates that CAS leaders imagined their work as a manly, moral enterprise centred on the dramatic, confrontational rescue of imperiled children from evil surroundings.